Through the looking glass and what Alice found there - Carroll, Lewis, 1832-1898.; Tenniel, Joun, 1820-1914. (New York : Macmillan and Co., 1872)
In this sequel to "Alice in Wonderland," Alice goes through the mirro to find a strange world where curious adventures await her.
Keywords: Fantasy